2021
DOI: 10.2478/eces-2021-0002
|View full text |Cite
|
Sign up to set email alerts
|

Do We Still Need a Laboratory to Study Advanced Oxidation Processes? A Review of the Modelling of Radical Reactions used for Water Treatment

Stanisław Wacławek

Abstract: Environmental pollution due to humankind’s often irresponsible actions has become a serious concern in the last few decades. Numerous contaminants are anthropogenically produced and are being transformed in ecological systems, which creates pollutants with unknown chemical properties and toxicity. Such chemical pathways are usually examined in the laboratory, where hours are often needed to perform proper kinetic experiments and analytical procedures. Due to increased computing power, it becomes easier to use … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 110 publications
(155 reference statements)
1
9
0
Order By: Relevance
“…In order to understand the impact of human activity on nature, scholars have contributed 10 research articles, presented in this special issue of the Ecological Chemistry and Engineering S (ECES). Specifically, Wacławek [2] provided an overview of the existing computational methods for describing the oxidative degradation of pollutants in terms of advanced oxidation processes (AOP, i.e., techniques utilizing OH radical for degradation of pollutants). The regioselectivity of the Acid Blue 129 compound is discussed as an example, and it was concluded that with the development of the information technology age, quantum chemical calculations (QCC) will not only become more accurate and accessible, but will also replace most of the experimental studies related to pollutant remediation in the future.…”
mentioning
confidence: 99%
“…In order to understand the impact of human activity on nature, scholars have contributed 10 research articles, presented in this special issue of the Ecological Chemistry and Engineering S (ECES). Specifically, Wacławek [2] provided an overview of the existing computational methods for describing the oxidative degradation of pollutants in terms of advanced oxidation processes (AOP, i.e., techniques utilizing OH radical for degradation of pollutants). The regioselectivity of the Acid Blue 129 compound is discussed as an example, and it was concluded that with the development of the information technology age, quantum chemical calculations (QCC) will not only become more accurate and accessible, but will also replace most of the experimental studies related to pollutant remediation in the future.…”
mentioning
confidence: 99%
“…Then, the hydroxyl radicals (HO) and the superoxide radicals (O2) were generated by UV light. The electron transfer between dye and the radicals on the surface accelerated the photodegradation rate of the reaction 48,49 . The photocatalysis of PS/TiO 2 in the presence of TEGDMA was increased due to the TEGDMA association with the self‐organization structure of the hybrid system, as seen in the SEM image in Fig.…”
Section: Resultsmentioning
confidence: 93%
“…As a result of visible-light irradiation of the Ag@biochar nanocomposite, electron–hole pairs were formed due to the SPR phenomenon of AgNPs generating ROS such as superoxide anions ( • O 2 – ) and hydroxyl radicals ( • OH) via the reaction of free electrons (e – ) with oxygen and the reaction of h + with H 2 O molecules adsorbed onto the Ag@biochar nanocomposite, respectively, which in turn initiate the photocatalytic degradation of the adsorbed MB molecules. Moreover, the reaction of visible light with oxygen (O 2 ) could result in the formation of other ROS such as the singlet oxygen ( 1 O 2 ) that further improves the photodegradation of MB. , A schematic representation of the possible mechanism for the photocatalytic degradation of MB on Ag@biochar is shown in Figure S4 …”
Section: Resultsmentioning
confidence: 99%